NOMINATE and American Political Development: A Primer. Issue 2 (22nd July 2016) - Everson, Phil; Valelly, Rick; Vishwanath, Arjun; Wiseman, Jim
Abstract : Steady political polarization since the late 1970s ranks among the most consequential transformations of American politics—one with far-reaching consequences for governance, congressional performance, the legitimacy of the Supreme Court, and citizen perceptions of the stakes of party conflict and elections. Our understanding of this polarization critically depends on measuring it. Its measurement in turn began with the invention of the NOMINATE algorithm and the widespread adoption of its estimates of the ideal points of members of Congress. Although the NOMINATE project has not been immune from technical and conceptual critique, its impact on how we think about contemporary politics and its discontents has been extraordinary and has helped to stimulate the creation of several similar scores. In order to deepen appreciation of this broadly important intellectual phenomenon, we offer an intuitively accessible treatment of the mathematics and conceptual assumptions of NOMINATE. We also stress that NOMINATE scores are a major resource for understanding other eras in American political development (APD) besides the current great polarization. To illustrate this point, we introduce readers to Voteview, which provides two-dimensional snapshots of congressional roll calls, among other data that it generates. We conclude by sketching how APD scholarship might contribute to the contemporary polarization discussion. Placing polarization and depolarization in historical perspective may powerfully illuminate whether, how, and why our current polarization might recede.